1992
DOI: 10.1203/00006450-199204000-00002
|View full text |Cite
|
Sign up to set email alerts
|

Ontogeny of the Epidermal Barrier to Water Loss in the Rat: Correlation of Function with Stratum Corneum Structure and Lipid Content

Abstract: ABSTRACT. The mammalian epidermal permeability barrier is provided by highly hydrophobic lipids forming multiple membrane bilayers within the extracellular domains of the outer, cornified cell layers. To characterize the critical events associated with barrier maturation, we correlated the emergence of a competent barrier to transepidermal water loss with development of the lamellar body secretory system, the organization of stratum corneum membrane bilayers, and the lipid composition of these membranes in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
79
0

Year Published

1996
1996
2012
2012

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(87 citation statements)
references
References 50 publications
8
79
0
Order By: Relevance
“…Newborn pups were removed individually from the litter, in approximately 24 h intervals following birth. Fetal tissue samples were generated by cesarean section, as described earlier (Aszterbaum et al, 1992). 2 0 ,7 0 -bis(carboxyethyl)-5,6-carboxyfluorescein (BCECF) was from molecular probes (Eugene, OR).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Newborn pups were removed individually from the litter, in approximately 24 h intervals following birth. Fetal tissue samples were generated by cesarean section, as described earlier (Aszterbaum et al, 1992). 2 0 ,7 0 -bis(carboxyethyl)-5,6-carboxyfluorescein (BCECF) was from molecular probes (Eugene, OR).…”
Section: Methodsmentioning
confidence: 99%
“…Rats have served as a useful model to examine a range of parameters of the peri-and neonatal adaptation process (Aszterbaum et al, 1992;Hoath et al, 1993;Wickett et al, 1993;Hanley et al, 1997). These studies have shown that the epidermal permeability barrier develops late in gestation, paralleled by increased expression of pH-dependent, lipid-processing enzymes.…”
mentioning
confidence: 99%
“…Earlier investigations had shown that the time course of skin barrier formation allowed the analysis of correlative changes in epidermal morphology (Aszterbaum et al, 1992). To validate our observations of an unaltered suprabasal development in the absence of K5, we performed a dye permeability Figure 6.…”
Section: Barrier Formation In K5 ؊/؊ Mice Is Not Disturbedmentioning
confidence: 99%
“…Although lung surfactant contains predominantly phospholipids, a class of lipids absent from barrier lipids, both secretory systems deliver lipid to their respective extracellular domains (1)(2)(3)(12)(13)(14). Moreover, the epidermal and lung lamellar secretory systems exhibit striking similarities in their developmental timetables, with both maturing in the third trimester in humans and other animals (4,(8)(9)(10)(11)15). In the fetal rat, lamellar bodies first appear in skin and lung on gestational d 18; secretion begins on d 19 and 20, respectively; and maturation of both tissue systems is complete by d 21 of gestation (normal parturition occurs on d 22) (15,16).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the epidermal and lung lamellar secretory systems exhibit striking similarities in their developmental timetables, with both maturing in the third trimester in humans and other animals (4,(8)(9)(10)(11)15). In the fetal rat, lamellar bodies first appear in skin and lung on gestational d 18; secretion begins on d 19 and 20, respectively; and maturation of both tissue systems is complete by d 21 of gestation (normal parturition occurs on d 22) (15,16). Furthermore, glucocorticoids and thyroid hormone accelerate lung maturation (reviewed in reference 17), and, as we have shown, glucocorticoids accelerate epidermal barrier maturation in utero in the rat (18), and both glucocorticoids and thyroid hormone accelerate fetal rat barrier formation in vitro (19).…”
Section: Introductionmentioning
confidence: 99%